Categories, applications, and potential of stem cells in bone regeneration: an overview - Jiao, Mingyang; Shuai, Ting; Zhao, Zhongfang; Wu, Yuwei; Yu, Linwei; Sun, Jingwen; De Caro, Raffaele; Macchi, Veronica; Porzionato, Andrea; Stocco, Elena; Jin, Chanyuan (Frontiers in Medicine, 2025)
Bone defects affect many individuals globally and can result in significant suffering and impairment, particularly among the elderly population. In addition, current treatment options for critical-size bone defects, such as autologous or allogeneic bone graft transplantation, present significant challenges. Within this clinical scenario the identification of novel and effective approaches for bone regeneration is urgently needed, and options derived from tissue engineering may be particularly appealing. Bone tissue engineering for bone regeneration involves the application of seed cells, growth factors, and biomaterials to create bioactive substitutes for repairing bone defects. In recent decades, advancements in stem cell research and biological biomaterials have led to remarkable breakthroughs in the field of bone regeneration. In particular, various categories of stem cells have been isolated, characterized, and employed in tissue engineering approaches. This review summarizes the applications of the main types of stem cells currently used for bone regeneration through tissue engineering approaches, and it also pays attention to the most appealing materials for it.